Analisis Efektivitas Insentif Ekonomi terhadap Upaya Pelestarian SDA dan Mitigasi Kerusakan Lingkungan - Satria Lam Syafi’i Simamora; Imsar Imsar (STIKes Ibnu Sina Ajibarang, 2025)
This study uses the library research qualitative method to examine the effectiveness of economic incentives in encouraging the conservation of natural resources (SDA) as well as mitigating environmental damage in a sustainable manner. The background of this study is driven by the increasing environmental degradation due to uncontrolled exploitation of natural resources, which is often oriented towards short-term profits without regard for ecological sustainability and community welfare. In this context, economic incentives are seen as a strategic policy instrument that is able to influence the behavior of business actors and society towards a more environmentally friendly and socially responsible activity pattern. Various forms of economic incentives were discussed including green subsidies, environmental taxes, payment for environmental services (PES) schemes, and ecolabel certification. These instruments are considered to be able to internalize the external costs of environmental damage into economic calculations, thereby providing pressure and motivation for business actors to implement more sustainable and innovative practices. Based on a review of academic literature, scientific journals, as well as national and international policies, it was found that the implementation of economic incentives has proven to be effective in increasing environmental awareness and encouraging green innovation significantly. However, the effectiveness of its implementation is highly dependent on the quality of policy governance, the level of transparency, regulatory clarity, and the active involvement of local communities. Without adequate oversight, incentives have the potential to be abused or not achieve their intended goals. Therefore, the design of economic incentive policies must be fair, measurable, and prepared with a participatory approach and based on empirical data. This study concludes that economic incentives not only function as a financial mechanism, but also as an instrument of behavior change, economic culture, and environmental innovation towards sustainability.